Effects of recurrent rainfall shocks on poverty and income distribution in rural Ecuador - Llerena Pinto, Maria Cristhina; Mirzabaev, Alisher; Qaim, Matin (Elsevier, 2025)
Climate change is associated with an increasing frequency of extreme weather events, which can severely reduce people’s welfare, especially in the Global South. Here, we analyze the impacts of rainfall shocks – including droughts and excessive rains – on economic and social outcomes, using micro-level panel data from rural Ecuador. We employ high-resolution weather information and georeferenced household survey data covering the period 2013–2019 to examine how single and repeated rainfall shocks affect income and poverty levels. Panel data regression models with household fixed effects show that rainfall shocks reduce per capita income by 9 % on average. The income losses are larger for poor households, agricultural households, and those involved in the informal sector. Two consecutive rainfall shocks have stronger negative income effects, especially for poor households with limited resilience capacity to recover quickly. Our estimates suggest that a second rainfall shock reduces the income among the poor by more than 50 %. Recurrent rainfall shocks also increase the poverty rate, the poverty gap, and poverty severity. These results highlight the need to consider heterogeneity in research and policymaking to understand and enhance people’s climate resilience.